PEMANFAATAN PEER GROUP SEBAGAI UPAYA MENEKAN JUMLAH PERKAWINAN CAMPURAN SECARA SIRRI - Putu Samawati; Wahyu Ernaningsih; Suci Flambonita; Vera Novianti (Ekasakti Jurnal Penelitian dan Pengabdian, 2022)
Abstract: The increasing number of mixed marriages without document (nikah sirri) in Muaraenim Regency, South Sumatra Province is a main note, especially with regard to the issue of legal protection for women and children who was born from such marriages. Globalization is a major factor in increasing the number of mixed marriages. The formation of peer groups in adolescents as agents of change that can assist in providing socialization and at the same time help provide understanding and protection for their peers is one strategy that can be done to reduce the number of mixed marriages in a sirri manner. The FH-UNSRI Extension Team carried out community service with mentoring training methods for youth groups and mosque youth associations in Muaraenim. The aim is to provide an understanding and insight into the regulation of mixed marriages and the impact of mixed marriages that are more detrimental to women and children. In addition, assistance mechanisms are also provided for victims of mixed marriages who wish to claim their rights. It is hoped that this peer group can help provide socialization and protection for people who are disadvantaged in their community, especially for victims of mixed marriages. Socialization is the key to reduce the number of mixed marriages, which are mostly unknown to teenagers. Abstrak: Meningkatnya jumlah perkawinan campuran secara sirri di Kabupaten Muaraenim Provinsi Sumatera Selatan menjadi catatan tersendiri, khususnya berkaitan dengan persoalan perlindungan hukum bagi para wanita dan anak-anak yang dilahirkan dari perkawinan tersebut. Globalisasi menjadi faktor utama dalam peningkatan jumlah perkawinan campuran sirri. Pembentukan peer group pada remaja sebagai agen perubahan yang dapat membantu dalam memberikan sosialisasi dan sekaligus membantu memberikan pemahaman dan perlindungan bagi teman sebayanya merupakan salah satu strategi yang dapat dilakukan untuk menekan jumlah perkawinan campuran secara sirri. Tim Penyuluh FH-UNSRI melaksanakan pengabdian kepada masyarakat dengan metode pelatihan pendampingan kepada kelompok remaja karang taruna dan ikatan remaja masjid di Muaraenim. Tujuannya memberikan pemahaman dan wawasan mengenai pengaturan perkawinan campuran dan dampak perkawinan campuran sirri yang lebih banyak merugikan wanita dan anak-anak. Selain itu juga diberikan mekanisme pendampingan bagi korban perkawinan campuran sirri yang ingin menuntut haknya. Harapannya peer group ini dapat membantu memberikan sosialisasi dan perlindungan bagi orang-orang yang dirugikan dalam lingkungan masyarakat mereka, khususnya bagi korban perkawinan campuran. Sosialisasi menjadi kata kunci untuk menekan jumlah perkawinan campuran sirri yang sebagian besar tidak diketahui dampaknya oleh para remaja.